Strategi Organisasi Formal Menjaga Ketahanan Institusi Lokal Di Pasar Raya Padang - Marleni Marleni (LPPM Universitas PGRI Sumatera Barat, 2015)
Market is an institution that was important in economic institutions. In addition, the market also a place of social and economic activity, the market serves to confront the economic players. Market and function as an economic facilities the benchmark for the sake of s income in the region . Problems traditional markets complex, all these problems rises on the weakness in traditional market management. Problems at the traditional market will cause endurance markets be weak. After the earthquake 2009 in west sumatera, problems at traditional markets especially in the Padang city of the getting uncontrollable. This article will review the strategy of a formal organization namely the office of market Â to persistence in maintaining traditional markets. As for strategy is provided by office of market Â to persistence in maintaining traditional markets include: a) infrastructure improvements, b) allocate time trading, c) moving fruit traders to duta merlin street , d ) guidance market traders